ANALISIS KINERJA KEPALA SUBBAGIAN TATA USAHA DAN STAF TATA USAHA DI SMA NEGERI 6 KOTA JAMBI - Rida Restu Restalillah; Sofyan Sofyan; Hansein Arif Wijaya (STKIP Pesisir Selatan, 2026)
This study aims to analyze the performance of the Head of the Administration Subdivision and Administrative Staff at SMA Negeri 6 Jambi City, identify obstacles that affect performance, and examine strategies implemented to overcome existing obstacles to support the effectiveness of school administrative services.: This study uses a qualitative method with a case study approach. Data in this study were obtained through observation, interviews, and document studies. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions by means of source triangulation and technical triangulation to ensure data validity. The results of the study indicate that the performance of the Head of the Administration Subdivision at SMA Negeri 6 Jambi City is in the very good category based on indicators of work quality, work quantity, timeliness, effectiveness of resource utilization, need for supervision, and personal integrity. Meanwhile, the performance of the Administrative Staff at SMA Negeri 6 Jambi City is in the fairly good to good category, although there are several aspects that need to be improved, especially in the aspects of time discipline, technology utilization, and archiving systems. The novelty of this study lies in the integrated analysis of administrative performance, as well as strategies to overcome obstacles and improve the effectiveness of school administrative services.